Vascular Aging and Hemodynamic Stability in the Intraoperative Period - Gragasin, Ferrante S.; Bourque, Stephane L.; Davidge, Sandra T. (Frontiers in Physiology, 2012)
The proportion of elderly people in the population is steadily increasing, and the inevitable consequence is that this subpopulation is more frequently represented in common medical procedures and surgeries. Understanding the circulatory changes that accompany the aging process is therefore becoming increasingly timely and relevant. In this short review, we discuss aspects of vascular control in aging that are particularly relevant in the maintenance of intraoperative hemodynamic stability. We subsequently review the effects of certain notable anesthetic agents with respect to the aging vasculature.